2007
DOI: 10.1073/pnas.0609204104
|View full text |Cite
|
Sign up to set email alerts
|

Topological locking restrains replication fork reversal

Abstract: Two-dimensional agarose gel electrophoresis, psoralen crosslinking, and electron microscopy were used to study the effects of positive supercoiling on fork reversal in isolated replication intermediates of bacterial DNA plasmids. The results obtained demonstrate that the formation of Holliday-like junctions at both forks of a replication bubble creates a topological constraint that prevents further regression of the forks. We propose that this topological locking of replication intermediates provides a biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…All the immunograms were aligned attending to the mobility of OCs. Note that chloroquine's intercalation has no effect on the electrophoretic mobility of nicked unreplicated molecules (29,37,50).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the immunograms were aligned attending to the mobility of OCs. Note that chloroquine's intercalation has no effect on the electrophoretic mobility of nicked unreplicated molecules (29,37,50).…”
Section: Resultsmentioning
confidence: 99%
“…6). As mentioned previously, it should be noticed that for RIs containing three-way junctions, once all the native (Ϫ)-supercoiling is removed, these molecules cannot acquire (ϩ)-supercoiling because the nascent strands of the sister duplexes form a fourth arm leading to fork reversal with changes in neither mass nor electrophoretic mobility (50,51). Finally, the number and complexity of replication knots were higher for the RIs isolated from DH5␣FЈ cells, DH5αF' (RecA -Topo IV + Gyr Nal ) grown at 37ºC r FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown, however, that formation of Holliday-like junctions at both forks of a replication bubble creates a topological constraint that prevents further regression of the forks (33). To confirm this observation for a different plasmid, we used a modification of two-dimensional gels where the agarose lane containing the DNA that came out from the first dimension was heated at 65°C in the presence of 0.1 M NaCl for 4 h before the second dimension took place (33,36). This condition favors branch migration and extrusion of the fourth arm of Holliday junctions in vitro (37,38).…”
Section: Resultsmentioning
confidence: 99%
“…The RIs of plasmids where the fork stalls at a specific site accumulate, generating a prominent signal in two-dimensional gel autoradiograms that can be readily distinguished on top of the simple-or double-Y patterns (7, 30 -32). Analysis of these plasmids undigested and after restriction enzyme digestion revealed that RFR readily forms in vitro but that fork retreat is severely limited in covalently closed domains (33). Extensive retreat and total extrusion of the nascent-nascent duplex, on the other hand, occurs spontaneously after nicking or restriction enzyme digestion.…”
Section: Replication Fork Reversal (Rfr)mentioning
confidence: 99%
“…It would now be interesting to know if trinucleotide repeats that form strong secondary structures, like (CCG) n and (GAA) n , are also able to induce fork reversal in vivo or if this is restricted to the more labile secondary structures formed by (CAG) n repeats. It is nevertheless interesting that fork reversal cannot occur spontaneously in supercoiled regions and could occur in vivo only if topoisomerases are present to relax the supercoiling induced by the progression of the replication fork (134,135).…”
Section: Vol 72 2008 Dna Repeats In Eukaryotes 707mentioning
confidence: 99%